2019
DOI: 10.1101/835918
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Germline and somatic genetic variants in the p53 pathway interact to affect cancer risk, progression and drug response

Abstract: 46Insights into oncogenesis derived from cancer susceptibility loci could facilitate 47 better cancer management and treatment through precision oncology. However, 48 therapeutic applications have thus far been limited by our current lack of 49 understanding regarding both their interactions with somatic cancer driver mutations 50 and their influence on tumorigenesis. Here, by integrating germline datasets relating 51 to cancer susceptibility with tumour data capturing somatically-acquired genetic 52 variation… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

6
2

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 79 publications
1
14
0
Order By: Relevance
“…Although most SNPs have only subtle effects, there is mounting evidence suggesting that they still contribute to the risk of developing cancer (13). Recently, we have shown that low-penetrant germline mutations in p53 pathway genes can directly control cancer related processes, including p53 activity and response to chemotherapies (14). Moreover, the Pan-Cancer Analysis of Whole Genomes (PCAWG) study found that 17% of all patients have rare germline variants associated with cancer (15).…”
Section: Introductionmentioning
confidence: 99%
“…Although most SNPs have only subtle effects, there is mounting evidence suggesting that they still contribute to the risk of developing cancer (13). Recently, we have shown that low-penetrant germline mutations in p53 pathway genes can directly control cancer related processes, including p53 activity and response to chemotherapies (14). Moreover, the Pan-Cancer Analysis of Whole Genomes (PCAWG) study found that 17% of all patients have rare germline variants associated with cancer (15).…”
Section: Introductionmentioning
confidence: 99%
“…Second, a loss of p53, due to inherited cancer risk polymorphisms, truncating mutations or allelic deletion in TP53, decreases the production rate of p53 (lowering α (Donehower et al, 2019; Livingstone et al, 1992; Macedo et al, 2016; Venkatachalam, 1998; X. Wang & Sun, 2017; P. Zhang et al, 2019)), dropping the system out of the Hopf subspace (Fig. 3C).…”
Section: Resultsmentioning
confidence: 99%
“…TP53 functional status was assessed based on somatic mutation and copy number alterations as described in Zhang et al 90 . TP53 mutation and copy number for the TCGA tumours were downloaded from cBioPortal (http://www.cbioportal.org).…”
Section: Multi-omics Discovery Cohortmentioning
confidence: 99%